Analisis Penggunaan Digital Marketing dalam Meningkatan Penjualan di Toko Pertanian Sari Tani Temanggung Jawa Tengah - Budi Lesmana; widiawati, santi (LPPM POLITEKNIK LP3I BANDUNG, 2025)
The purpose of this study is to analyze the effect of digital marketing on sales made at the Sari Tani Agricultural Store. Marketing has become one of the efficient ways for small and medium enterprises (SMEs) to optimize sales along with the development of digital technology. This type of research is quantitative which focuses on a survey approach involving consumers and Sari Tani store managers as respondents. Research data were collected through questionnaires, interviews and linear regression analysis to examine the relationship between digital marketing variables, including social media sites, e-commerce and paid advertising significantly. The results of this study indicate that the ability to optimize digital marketing has a significant effect on increasing the number of new customers, strengthening customer loyalty and having a direct impact on increasing sales at the Sari Tani Store. The regression analysis conducted shows that digital marketing strategies have a positive effect on sales. The conclusion of this study is to emphasize the importance of the role of digital marketing in increasing the competitiveness and sales growth of the Sari Tani store, as well as providing recommendations for optimizing digital marketing strategies on sales growth..